Poly pharmacology in Alzheimer's disease: A Modern Approach to Disease-Modifying Drug Development (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder and the most common cause of dementia, posing a significant global health burden with limited therapeutic options. The currently approved drugs primarily provide symptomatic relief without effectively halting disease progression due to the complex and multifactorial nature of AD, which involves amyloid-β plaque formation, tau hyperphosphorylation, cholinergic dysfunction, oxidative stress, mitochondrial impairment, excitotoxicity, and chronic neuro inflammation. Consequently, poly pharmacology has emerged as a promising drug discovery strategy that aims to develop single therapeutic agents capable of simultaneously modulating multiple pathological targets, thereby overcoming the limitations of conventional single-target therapies. This review highlights recent advances in poly pharmacological approaches for Alzheimer's disease, with particular emphasis on multi-target-directed ligands (MTDLs), hybrid molecules, natural-product-derived compounds, and drug repurposing strategies. Recent studies have demonstrated that compounds capable of concurrently inhibiting acetylcholinesterase, reducing amyloid-β aggregation, suppressing tau phosphorylation, attenuating oxidative stress, and modulating neuro inflammatory pathways exhibit enhanced neuroprotective potential and improved therapeutic efficacy in preclinical models. Furthermore, advances in medicinal chemistry, network pharmacology, molecular docking, virtual screening, and systems pharmacology have accelerated the identification and optimization of novel multi-target drug candidates with favourable pharmacokinetic and safety profiles. Although several promising candidates have shown encouraging preclinical outcomes, further experimental validation and well-designed clinical trials are necessary to establish their long-term efficacy and safety. Overall, poly pharmacology represents a transformative and rational approach for the development of disease-modifying therapies for Alzheimer's disease by addressing its complex molecular mechanisms, offering new opportunities
Keywords: Alzheimer's disease; Poly pharmacology; Multi-target-directed ligands; Disease-modifying therapy; Neurodegeneration; Drug discovery; Medicinal chemistry; Network pharmacology